Fr. Jerzy Popiełuszko - a victim of political repression or martyr for the faith - Milena Kindziuk (The Francis de Sales Scientific Society (TNFS.PL), 2017)
There is an ongoing debate on the character of Fr. Jerzy Popiełuszko's activity between 1980 and 1984, as well as the major motives for his abduction and murder on October 19, 1984 perpetrated by officers of the Security Service of the Ministry of Internal Affairs (Pol. SB). The present paper argues that treating this activity and death in a purely political way constitutes a fundamental misunderstanding of the priest's attitude or a conscious propaganda. An analysis of the priest's activities, motives behind his pastoral commitment, the course of the Holy Masses for the Fatherland as well as the content of his sermons, shows that he was guided by religious, pastoral and spiritual reasons, and his death was martyrdom for the faith.